Evaluation and decision making in a university library from performance indicators - Pereira, Carla Purcina de Campos; Varvakis, Gregorio (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
The purpose of using performance indicators in Brazilian university libraries is to provide information for decision making and to promote quality in the educational system. We analyzed the performance indicators used in 95 university libraries. Among them, the relevance of the indicators and their use in the decision-making process was assessed. The performance evaluation models were the performance indicators for the evaluation of university libraries based on “International Organization for Standardization 11.620/2008 Information and documentation – Library performance indicators”. It was evidenced that indicators are relevant for decision making. However, there is a discrepancy between their use and relevance. The set of indicators applied to university libraries is usually the same as those proposed by the Ministry of Education. An adequate management of the performance indicators and the application in the decision-making process promote the quality of the offered products and, therefore, the quality of the education of the higher education institutions. Keywords: Decision making. Performance indicators. Quality control. University libraries. Link: http://www.scielo.br/pdf/tinf/v30n2/0103-3786-tinf-30-2-0219.pdf